Repercussions of family violence: oral history of adolescents - Júlia Renata Fernandes de Magalhães; Nadirlene Pereira Gomes; Rosana Santos Mota; Raiane Moreira dos Santos; Álvaro Pereira; Jeane Freitas de Oliveira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To know the repercussions of the experience of family violence from the oral history of adolescents. Method: Qualitative study based on the Oral History method, conducted from interviews with adolescents enrolled in a public school in Salvador, State of Bahia, Brazil. The data were systematized according to the thematic analysis and supported by theoretical references on family violence and adolescence. Results: Family violence implies physical illness associated with the damage caused by physical aggression and somatization of violent events, as well as compromising mental health, provoking feelings of deep sadness, self-injury behavior and suicidal ideation. All of these factors impair interpersonal relationships, school performance, as well as making them more vulnerable to alcohol intake. Final Considerations: The study indicates signs suggestive of grievance, from which the professionals should proceed the investigation in order to refute or confirm the experience of the phenomenon, as well as intervene in the cases.